Back Cover: Plasma Process. Polym. 11∕2014. Issue 11 (November 2014) - Vandenabeele, Cédric; Maurau, Rémy; Bulou, Simon; Siffer, Frederic; Gérard, Mathieu; Belmonte, Thierry; Choquet, Patrick
<x xml:space="preserve">Abstract</x> Back Cover: Organo‐chlorinated thin films are produced from dichloromethane on zinc‐plated steel wires in a continuous‐flow AP‐DBD plasma process. High quality layers can be deposited at high deposition rates. A wide range of chlorinated species are created in the Ar discharge, ranging from small volatile gaseous molecules to large‐sized PAH. An increase in the injected energy induces a decrease in hydrogen concentration in the coating that becomes closer to a graphite structure. Further details can be found in the article by Simon Bulou et. al. on page 1089. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>